The Endogenous Skill Bias of Technical Change and Inequality in Developing Countries - Behar, Alberto (IMF Working Papers; Working Paper ;, 2013)
This paper draws on existing empirical literature and an original theoretical model to argue that globalization and skill supply affect the extent to which technology adoption in developing countries favors skilled workers. Developing countries are experiencing technical change that is skill-biased because skill-biased technologies are becoming relatively cheaper. Increased skill supply further biases technical change in favor of skilled labor. Free trade induces technology that favors skilled workers in skill-abundant developing countries and that favors unskilled workers in skill-scarce developing countries, and therefore amplifies the predicted wage effects of trade liberalization. These features aid our understanding of the observed rises in inequality within developing countries and the absence of a significant downward effect of expanded educational attainment on skill premia. They also help account for the large and differential effects of trade liberalization on inequality. These findings are pertinent for the Middle East and North Africa because of its recent increase in trade openness and remarkable rise in educational attainment.